A KCNQ4 c.546C>G Genetic Variant Associated with Late Onset Non-Syndromic Hearing Loss in a Taiwanese Population - Ting-Ting Yen (MDPI AG, 2021)
Clinical presentation is heterogeneous for autosomal dominant nonsyndromic hearing loss (ADNSHL). Variants of KCNQ4 gene is a common genetic factor of ADNSHL. Few studies have investigated the association between hearing impairment and the variant c.546C>G of KCNQ4. Here, we investigated the phenotype and clinical manifestations of the KCNQ4 variant. Study subjects were selected from the participants of the Taiwan Precision Medicine Initiative. In total, we enrolled 12 individuals with KCNQ4 c.546C>G carriers and 107 non-carriers, and performed pure tone audiometry (PTA) test and phenome-wide association (PheWAS) analysis for the patients. We found that c.546C>G variant was related to an increased risk of hearing loss. All patients with c.546C>G variant were aged >65 years and had sensorineural and high frequency hearing loss. Of these patients, a third (66.7%) showed moderate and progressive hearing loss, 41.7% complained of tinnitus and 16.7% complained of vertigo. Additionally, we found a significant association between KCNQ4 c.546C>G variant, aortic aneurysm, fracture of lower limb and polyneuropathy in diabetes. KCNQ4 c.546C>G is likely a potentially pathogenic variant of ADNSHL in the elderly population. Genetic counseling, annual audiogram and early assistive listening device intervention are highly recommended to prevent profound hearing impairment in this patient group.